Analisis Ideologi pada Teks Mitos Baris Cina di Desa Adat Renon - Anggara Wijaya, Putu Galang Nova; Nala Antara, I Gde (Humanis, 2020)
This study is entitled “Analisis Ideologi pada Teks Mitos Baris Cina di Desa Adat Renon”. This study aims to describe the structure of the teks mitos Baris Cina in Desa Adat Renon and analyzes the ideological meaning contained in it. The theories used in the study are structural theory and mythology theory. The stage of providing data used the field method, assised with interview technique, recording thecnique, note-taking technique, and idiomatic translation technique. The data are analyzed using qualitative method by descriptive-analytic technique. The data are presented using qualitative method by deductive technique. The structure of the teks mitos Baris Cina in Desa Adat Renon contsists of incidents, plot, character and characterization, setting, theme, and moral value. There is a connotation meaning in the teks mitos Baris Cina which then develops into a myth so that the myth is used as a way of life by the people as an ideology. The meaning of ideology contained in it is the institution’s guard, obligations, and historical relics.